IDENTIFICATION OF CALYSTEGINES IN PLANTS OF FAMILY ERICACEAE WITH GAS CHROMATOGRAPHY – MASS SPECTROMETRY METHOD - Покрышкин, Сергей Александрович; Струсовская, Ольга Геннадьевна; Asano, Naoki; Косяков, Дмитрий Сергеевич; Гаврилин, Михаил Витальевич; Мудрецова, Юлия (Химия растительного сырья, 2014)
The presence of calystegines in plant samples of family Ericaceae has been confirmed using gas chromatography - tandem mass spectrometry method. It was found that calystegine B2 presents in all samples tested and is dominant. Сalystegine B1 was found in cowberry and cranberry. The presence of calystegine B3 was convincingly confirmedonly in lingonberry.